2007
DOI: 10.2169/internalmedicine.46.6355
|View full text |Cite
|
Sign up to set email alerts
|

Association between Markers of Glycemic Control, Cardiovascular Complications and Survival in Type 2 Diabetic Patients with End-Stage Renal Disease

Abstract: Background and Objective The influence of glycemic control on cardiovascular (CV) complications or survival is not clear in diabetic patients with end-stage renal disease (ESRD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 35 publications
(18 reference statements)
2
44
2
2
Order By: Relevance
“…Some previous studies have shown the prognostic value of GA levels and the association between GA levels and progression of atherosclerosis in diabetic dialysis patients (20)(21)(22)(23). In the present study, the question of which is a better marker, HbA1c or GA, in diabetic CKD patients was not investigated.…”
Section: Discussionmentioning
confidence: 81%
“…Some previous studies have shown the prognostic value of GA levels and the association between GA levels and progression of atherosclerosis in diabetic dialysis patients (20)(21)(22)(23). In the present study, the question of which is a better marker, HbA1c or GA, in diabetic CKD patients was not investigated.…”
Section: Discussionmentioning
confidence: 81%
“…In place of HbA1c, glycated albumin (GA) has been shown to be a more accurate marker for glycemic control (6)(7)(8). Several studies have shown the association between mortality, the development of cardiovascular disease, and GA values in these patients (9,10). Other studies have shown the association between arterial stiffness, peripheral vascular calcification, and high GA values in these patients (11,12).…”
Section: Several Studies Have Shown the Association Between Poor Glycmentioning
confidence: 99%
“…An increase in advanced glycation of end products (AGEs) caused by hyperglycemia initiates injury to cells including vascular endothelium, glomeruli, and tubules, which facilitates the appearance of DN eventually. AGEs in the body can be assessed by measuring HbA1c; however, a reduction in levels of both HbA1c and blood glucose does not prevent the kidney from the development of ESRD (Okada et al 2007). Intensive control of blood glucose does not lead to a reduction in mortality of stroke and cardiovascular complications (Mannucci et al 2009), and no difference has been found in mortality between 6.9% of HbA1c in intensive therapy group and 8.4% of HbA1c in the standard therapy group (Duckworth et al 2009).…”
Section: Introductionmentioning
confidence: 99%